PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI A SDN 011 BUKIT GAJAH KECAMATAN UKUI - Rohlina Tambunan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low student learning outcomes IPA. Of the 20 students,only 7 students (42.31%) completed the study results, while the average student learningoutcomes is only 65.38. This study aims to improve science learning outcomes of studentswith the application of quantum teaching learning model. This research is a class act. Basedon the results of the study revealed that the learning outcomes and the activities of teachersand students has increased, the average value of the basic score 65.38 UH then the first cycleto 69.08 with an increase of 5.66%. While on the second cycle into 85.54 with an increase of23.83%. In the first cycle of the first meeting 66.7% (enough), at a meeting II increased to75% (good). In the second cycle the first meeting 83.3% (good), then at a meeting IIincreased to 95.8% (excellent). While the percentage of student activity also increased. In thefirst cycle of the first meeting 62.5% (enough), at a meeting II increased to 70.8% (good). Inthe second cycle the first meeting 79.2% (good), then at a meeting II increased to 91.7%(excellent).